Тhe Views of the Socialist Labour Party of Yugoslavia (Communists) and the Communist Party of Yugoslavia on the Kingdom of Serbs, Croats and Slovenes 1918 - 1920 - Petrović, Nenad Ž. (Sociološki pregled, 2019)
In this paper, we focus on the legal period of life and operation of the Communist Party of Yugoslavia in the first two years of the existence of the new state, we consider the period from December 1918 to December 1920 with a brief look at the later development of the opinions and views of this political organization on the national question during its illegal activity until 1941. For the development of this article, primary sources were used, such as party documents created during the first two congresses in 1919 and 1920, as well as relevant literature.
Keywords: Yugoslavia; national question; the Communist Party of Yugoslavia; “Announcement”